MASLAHAT MENURUT IMAM MALIK DAN IMAM AL-GHAZALI (STUDI PERBANDINGAN) - Andi Herawati (DIKTUM: Jurnal Syariah dan Hukum, 2014)
This article discusses Imam Malik’s and Imam al-Gazali’s theory of maslahat: First, both Malik and al-Gazali agreed that maslahat relevant to Islamic law. Therefore, maslahat must not contradict the primary texts (the Quran and hadith), rational and absolute, there is no primary text supports or contradicts it. Both Malik and al-Gazali agreed that maslahat only used in social aspect, not worship field. Second, Imam Malik used maslahah mursalah as a resorce of Islamic law. In contrast, al-Gazali put maslahah mursalah as method to Islamic law. Malik justified that maslahah mursalah as an independent Islamic resource, and al-Gazali justified it as a dependent lslam law resouce. Malik’s point of view is different from al-Gazali’s where Malik said that maslahah mursalah may be used both for daruriyat and hajiyat, while al-Gazali’s point of view that it is used for daruriyat or hajiyat which is the same level as daruriyat.